Species checklist of the subgenus Polistella of the paperwasp genus Polistes (Insecta: Hymenoptera: Vespidae, Polistinae) other than continental afrotropical and malagasy species - Nguyen, Lien T.P.; Carpenter, James M.; Kojima, Jun-ichi; D. Nguyen, Anh (Academia Journal of Biology, 2026)
A comprehensive and updated species checklist of the Old World subgenus Polistella of the genus Polistes (Hymenoptera: Vespidae) occurring in the areas other than the continental Africa and Madagascar is presented. The checklist compiles taxonomic and nomenclatural information as well as distributional data based on critical examinations of literature, particularly incorporating species described after Carpenter's (1996) distributional checklist of the genus Polistes. For each taxon, information on nomenclature, type locality, type depository, and distribution records are provided, along with remarks on taxonomic issues where they are necessary. During the compilation, the name Polistes (Polistella) daehanicus Kim, 2023 was found to be unavailable under the 4th edition of the International Code of Zoological Nomenclature without fulfilling the requirement of Article 16.4.2. Providing the name and location of the depository of the holotype, Dr. Kim has herein validated the name.